SARS-CoV-2 infection of intestinal epithelia cells sensed by RIG-I and DHX-15 evokes innate immune response and immune cross-talk - Zhang, Lijuan; Zhang, Yize; Wang, Ruiqin; Liu, Xiaoning; Zhao, Jinmeng; Tsuda, Masato; Li, You (Frontiers in Cellular and Infection Microbiology, 2023)
SARS-CoV-2 causes a spectrum of clinical symptoms from respiratory damage to gastrointestinal disorders. Intestinal infection of SARS-CoV-2 triggers immune response. However, the cellular mechanism that how SARS-CoV-2 initiates and induces intestinal immunity is not understood. Here, we exploited SARS-CoV-2-GFP/ΔN trVLP pseudo-virus system and demonstrated that RIG-I and DHX15 are required for sensing SARS-CoV-2 and inducing cellular immune response through MAVS signaling in intestinal epithelial cells (IECs) upon SARS-CoV-2 infection. NLRP6 also engages in the regulation of SARS-CoV-2 immunity by producing IL-18. Furthermore, primary cellular immune response provoked by SARS-CoV-2 in IECs further cascades activation of MAIT cells and produces cytotoxic cytokines including IFN-γ, granzyme B via an IL-18 dependent mechanism. These findings taken together unveil molecular basis of immune recognition in IECs in response to SARS-CoV-2, and provide insights that intestinal immune cross-talk with other immune cells triggers amplified immunity and probably contributes to immunopathogenesis of COVID-19.